Tribology - Lubricants and Lubrication 2011
DOI: 10.5772/20790
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Aspects of Rolling Bearing Failures

Abstract: Introduction Rolling (element) bearings are referred to as anti-friction bearings due to the low friction and hence only slight energy loss they cause in service, especially compared to sliding or friction bearings. The minor wear occurring in proper operation superficially seems to suggest the question how rolling contact tribology should be of relevance to bearing failures. Satisfactorily proven throughout the 20 th century primarily on small highly loaded ball bearings, the life prediction is actually base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
132
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(136 citation statements)
references
References 51 publications
4
132
0
Order By: Relevance
“…It should be noted that at this stage the butterfly progression is stopped in the model. This is an assumption consistent with most of the experimental observations that suggest cracks can propagate without further butterfly expansion [49]. However, it should be noted that in few cases it has been observed that butterflies wings keep expanding till final failure as shown in Fig.…”
Section: Model Application To Butterfly and Crack Progressionsupporting
confidence: 64%
“…It should be noted that at this stage the butterfly progression is stopped in the model. This is an assumption consistent with most of the experimental observations that suggest cracks can propagate without further butterfly expansion [49]. However, it should be noted that in few cases it has been observed that butterflies wings keep expanding till final failure as shown in Fig.…”
Section: Model Application To Butterfly and Crack Progressionsupporting
confidence: 64%
“…The proposed initiation and propagation mechanisms for WSF/WECs are: (1) surface initiation through two opposing mechanisms, (1) shear stress-induced fatigue microcracks [17] and (2) localised high circumferential tensile stress spontaneously induced cleavage-like axial cracks that initiate independently [5,17,18], at defects such as inclusions [17][18][19][20][21] or due to corrosion, machining defects or electrical erosion pits [21]; (2) subsurface initiation by non-metallic inclusions (NMIs) [5][6][7][22][23][24][25][26], perhaps in some cases due to tensile stresses [27]; (3) adiabatic shear banding independent or including defects through impact events, cracks forming after microstructural changes occur [2,28]; (4) self-charging of lubricants triggering localised transient current flow causing local electromagnetic induction that crosses the contact surface leading to electrothermal mechanisms triggering subsequent WEA microstructural change [29,30]; (5) a multistage initiation of WECs as a result of migration of carbon under shear stress and high localised energy [31].…”
Section: Introductionmentioning
confidence: 99%
“…Metallurgical research based on plastic alterations detected in subsurface material by transmission electron microscopic investigation gives indications that the subsurface depth at which significant amounts of material alteration occur is approximately 0.75b [18]. In summary, the region or zone of maximum shearing stresses can be defined as the stressed volume beneath the Hertzian contact ranging from 0.50 to 0.79b depth below the stressed surface.…”
Section: Depth To Critical Shearing Stressmentioning
confidence: 99%